CSI, crime scene investigation. The complete first season [videorecording (DVD)] - Zuiker, Anthony E., 1968- (Paramount Pictures : CBS DVD, 2003)
Contains the 23 first-run episodes of the entire first season of CSI. Witness how the evidence of crime can "see" the truth